Agreement of Central Corneal Thickness Measurements between Scheimpflug Photography and Optical Low-Coherence Reflectometry in Children. (18th May 2020) - Hashemi, Hassan; Nabovati, Payam; Khabazkhoob, Mehdi; Emamian, Mohammad Hassan; Yekta, Abbasali; Fotouhi, Akbar
ABSTRACT: Purpose: Central corneal thickness (CCT) is a key indicator of the corneal health status and is therefore of clinical importance. The aim of the present study was to determine the agreement between Scheimpflug photography (SP) and optical low-coherence reflectometry (OLCR) systems in measuring the CCT in children. Methods: In this cross-sectional study, the samples were selected from Shahroud schoolchildren using cluster sampling. The samples then underwent optometric examinations, including the measurement of visual acuity and refraction. CCT measurements were done by the SP and OLCR systems between 8 am and 4 pm. To evaluate the agreement between these devices, 95% limits of agreement (LoA) and interclass correlation coefficient (ICC) were reported. Results: After applying the exclusion criteria, 4890 right eyes (53.2% male) were analyzed. The mean age of the students was 9.22 ± 1.72 years (range: 6–12 years). The mean CCT by the SP and OLCR systems was 555.30 ± 34.15 and 550.23 ± 35.11 µm, respectively. The 95% LoA between the two devices was −19.81 to 9.66 µm, and the ICC was 0.983. The CCT difference between the SP and OLCR systems was 5.61 µm in boys and 3.36 µm in girls. The CCT difference between the two devices was 6.41 µm in 6-year-old and 3.54 µm in 12-year-old children. The 95% LoA was −17.96 to 9.58 µm and −18.89 to 8.47 µm and the ICC was 0.987 and 0.984 in myopic and hyperopic subjects, respectively. Conclusion: The results of this study showed a high agreement between OLCR and SP measurements of CCT in children.